Implementasi Penilaian Hasil Belajar PAI BP pada Kurikulum Merdeka di SMK Ma’arif NU 1 Cilongok Kabupaten Banyumas - Nisfi Hami Saefudin; Suwito Suwito (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The implementation of the Merdeka Curriculum (Merdeka Curriculum) maximizes student learning and strengthens competencies, aiming to restore education in Indonesia after the COVID-19 pandemic. SMK Ma'arif NU 1 Cilongok, Banyumas Regency, implemented the Merdeka Curriculum starting in 2021. This has resulted in several impacts that have become problematic in educational activities at SMK Ma'arif NU 1 Cilongok, Banyumas Regency. The purpose of this study was to analyze the implementation of Islamic Religious Education (PAI) learning outcome assessment using the Merdeka Curriculum at SMK Ma'arif NU 1 Cilongok, Banyumas Regency. Furthermore, it was also to understand the Islamic Religious Education (PAI) learning process using the Merdeka Curriculum. The results of this study indicate that the implementation of the Merdeka Curriculum learning outcome assessment at SMK Ma'arif NU 1 Cilongok, Banyumas Regency, encompasses diagnostic, formative, and summative assessments. The assessment also includes several steps, from planning and creating a framework to evaluating student learning outcomes. Based on this research, student learning outcomes have improved compared to when implementing the 2013 curriculum. In implementing the independent curriculum, there are several obstacles, including student readiness to take part in digital-based assessments.   Keywords: Merdeka Curriculum, Islamic Religious Education (PAI) Learning Outcomes